The tremendous contribution of biosciences and biotechnology for better life: research dissemination is one of the most important role to make it happen - Elfahmi (Current Research on Bioscences and Biotechnology, 2019)
Biosciences and biotechnology have become the interesting topics since long to be investigated in order to understand science and technology, develop many tools and instrumentation, discovery of new drugs including natural base drugs and biopharmaceutical, contribute in energy sources, interact with the environment as well as to improve the quality of human being. The researches of the field have dramatically contributed for many other field and for better life. Uncounted numbers publications in these field will be continuously rising. To contribute in dissemination of research output which have been done by researcher around the world, the Current Research on Biosciences and Biotechnology so called CRBB is published in this year. In the beginning this journal will publish 2 issue in the year and will be increased in the future. All researchers in the field of bioscience and biotechnology are invited to submit the manuscripts to CRBB. The manuscript will be peer reviewed prior to publish.